Iron and vitamin D status in breastfed infants and their mothers - Kang, Yu Sun (Korean J Pediatr, 2015)
PURPOSE: We assessed the relationships between iron and vitamin D statuses in breastfed infants and their mothers and evaluated the determinants of iron and vitamin D deficiencies in breastfed infants. METHODS: Seventy breastfed infants aged 4-24 months and their mothers participated in this study from February 2012 to May 2013. Complete blood counts, total iron binding capacity, and levels of C-reactive protein, iron, ferritin, calcium, phosphate, alkaline phosphatase, and 25-hydroxyvitamin D (25(OH)D) in infants and their mothers were measured. RESULTS: A history of maternal prepregnancy anemia was associated with lower ferritin and 25(OH)D levels in both infants and their mothers. The 25(OH)D level of infants correlated with maternal 25(OH) D levels. The independent risk factors for iron deficiency in breastfed infants were the duration of breastfeeding (odds ratio [OR], 6.54; 95% confidence interval [CI], 1.09-39.2; P=0.04) and infant body weight (OR, 2.65; 95% CI, 1.07-6.56; P=0.04). The determinants for vitamin D deficiency were the infant's age (OR, 0.15; 95% CI, 0.02-0.97; P=0.046) and maternal 25(OH)D level (OR, 0.74; 95% CI, 0.59-0.92; P=0.01). CONCLUSION: A maternal history of prepregnancy anemia requiring iron therapy was associated with lower current ferritin and 25(OH)D levels in both infants and their mothers. Therefore, physicians should monitor not only iron but also vitamin D levels in infants who are breastfed by mothers who had prepregnancy anemia.